2017
DOI: 10.7146/fppu.v1i2.97715
|View full text |Cite
|
Sign up to set email alerts
|

Statens eller familiens børn? Tvang og omsorg i mødet mellem nytilkomne familier og danske daginstitutioner

Abstract: ResuméNytilkomne familier bliver mødt med mange krav fra den danske velfærdsstat. Et af kravene er, at de skal sende deres 0-6 årige børn i dagtilbud, så forældrene kan gå på sprogskole eller komme i praktik. Artiklen belyser nogle af de dilemmaer, der opstår i forældresamarbejdet i mødet mellem pædagoger og nytilkomne familier. Disse dilemmaer udspringer af den myndighedsrolle som pædagogerne har, samtidig med at de ofte får en tæt relation til forældrene, og har et oprigtigt ønske om at hjælpe både børn og f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 0 publications
0
8
0
1
Order By: Relevance
“…Immediately upon arrival in Denmark, refugees are expected to take part in an integration program, and children must be enrolled in day-care or school (Bregnbaek et al 2017). As in other Scandinavian countries, day-care is regarded as an integral part of the healthy development of children.…”
Section: Parental Cooperation and Intimate Distancesmentioning
confidence: 99%
“…Immediately upon arrival in Denmark, refugees are expected to take part in an integration program, and children must be enrolled in day-care or school (Bregnbaek et al 2017). As in other Scandinavian countries, day-care is regarded as an integral part of the healthy development of children.…”
Section: Parental Cooperation and Intimate Distancesmentioning
confidence: 99%
“…Mikkel Rytter has argued that in Denmark, the expectation that immigrants should adapt as fast as possible to the cultural norms of sameness, paradoxically works to reinforce their otherness (Rytter, 2018). In the context of day care institutions, anthropological studies have shown that educational and institutional practices rationalized with reference to, for instance, health, well-being or learning, often reflect the middle class values and practices of the white majority (Bregnbaek et al, 2017;Palludan, 2007, Jørgensen & Martiny-Bruun, 2019Sparrman et al, 2016). Expectations of sameness mean that social differences related, for instance, to language or parenting practices, are considered problematic.…”
Section: "Nature-foreign" Children and Parentsaccess And Inclusion In The Gardenmentioning
confidence: 99%
“…Expectations of sameness mean that social differences related, for instance, to language or parenting practices, are considered problematic. As a result, minority children and parents are met with "language tones" (Palludan, 2007) and patterns of cooperation ( Bregnbaek et al, 2017) different from those involving majority children and parents, hereby creating and reinforcing processes of exclusion rather than inclusion. Nature education, we argue, is one area in which such exclusionary processes are at work.…”
Section: "Nature-foreign" Children and Parentsaccess And Inclusion In The Gardenmentioning
confidence: 99%
See 2 more Smart Citations